Feedback during learning and performance of jump test - Poderys, J.; Trinkunas, E.; Poderyte, K.; Silinskas, V. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The purpose of this presentation is to introduce others about the possibilities of developed system designed for the registration and measurements of body movements. The developed system based on accelerometer measurements allows assessing the performance of tasks, to measure the acceleration and the speed of body movements.